Jana ze Stobnicy (1470–1519) wykład o Grecji. Inspiracje Eneasza Sylwiusza Piccolominiego (1405–1464) - Zawadzki, Robert K. (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2018)
The article offers insights on the reception and cultural transmission of one of the most important Renaissance texts entitled De Europa written by Aeneas Silvius Piccolomini, an Italian scholar (he became Pope Pius II in 1458). His work was adopted and adapted by the Polish scholar Jan of Stobnica. In his dissertation Introductio in Ptolemaei cosmographiam cum longitudinibus et latitudinibus regionum et civitatum celebriorum, he took up all issues of Piccolomini`s treatise, including geographical and historical aspects of Greece. His attitude to this material was very positive. The article considers the motifs of Greek districts, such as Macedonia, Thessaly, Boeotia, Attica, the Peloponnese, the Isthmus, Achaea, Acarnania, Epirus, and the significance of Greece for Polish Renaissance culture.